Influence of cohesive stresses on shear capacity of reinforced SFRC beams without stirrups: A discrete crack approach. (1st February 2019) - Gali, Sahith; Subramaniam, Kolluru V.L.
Highlights: Multi-linear stress-crack separation (σ − Δw) relationship of steel fiber reinforced concrete obtained. Cracking in steel fiber reinforced concrete (SFRC) shear beam is evaluated using digital image correlation. Dilatancy directly measured from shear crack. Cohesive crack closing stress provides crack control and increase contact stress on primary shear crack faces. The σ − Δw relationship from tensile fracture provides accurate prediction of the shear capacity. Abstract: An experimental investigation on the fracture behavior and the dilatant crack opening in the shear response of concrete with discrete steel fiber reinforcement is presented. Hooked-ended steel fibers are used at 0.5% and 0.75% volume fractions. From the experimental fracture response of steel fiber reinforced concrete beams, the cohesive stress-crack opening relationship is derived using the cracked hinge model. Load tests are conducted on laboratory-sized reinforced concrete beams without steel stirrups, designed to fail in shear. The crack growth and propagation in the shear behavior of concrete with and without fibers are evaluated from displacements measured using digital image correlation (DIC). The in-situ dilatant behavior of the shear crack is established from the slip and the crack opening displacements measured across the critical shear crack. A discrete crack-based formulation with internal contact forces on the crack faces and cohesive stress from fibers is developed for predicting the shear capacity of a reinforced concrete beam. The discrete crack-based model is derived using the physical observation on cracks in the reinforced concrete beams. The prediction of the model includes an increase in the contact forces with an increase in the fiber force at peak shear resistance with an increasing volume fraction of fibers. The additional contact forces mobilized across the crack by the fibers maintains the shear transfer across the crack and hence the load carrying capacity is sustained for a larger crack opening. The model derived from laboratory-sized specimens accurately predicts the scaling of the shear capacity with the size of the beam.